Differences in Halal Food Consumption Behavior with Providing Leaflet and Flashcard Media Education to Students - Hilda Alfina Istiqomah; Endah Budi Permana Putri (UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2023)
Most teenagers choose to consume food products that do not have a halal logo because theyare closer to where they live. This research aims to analyze differences in halal food consumption behavior using media education leaflets and flashcards on the Faculty of education students at Nahdlatul Ulama University, Surabaya. The type of this research is true Experimental Design by using a Repost Test Design. The number of samples in this study was 66 respondents. Sampling in this study used techniques, of simple random sampling. Then divided into 33 respondents for group leaflets and 33 respondents for, group flashcards. The test analysis used is test Mann Whitney with a significant level (?=0.05). The result of This research shows that there is no difference in behavior between media groups leaflets and flashcards(p=0.090). Providing education with media leaflets and flashcards can increase halal food, consumption behavior among students. It is hoped that there will be further research using different, media such as audio-visual in looking at halal food consumption behavior.